MASALAH TIDUR ANAK DENGAN LEUKEMIA LIMFOBLASTIK AKUT DALAM MENJALANI KEMOTERAPI FASE INDUKSI - Andrye Fernandes (LPPM UNIVERSITAS PERINTIS INDONESIA, 2019)
Chemotherapy has an effect on the occurrence of sleep disorders in children who suffer from acute lymphoblastic leukemia. Sleep disorders experienced by children have an impact on optimizing the long-term quality of life of children. This study aims to describe sleep problems that occur in children suffering from acute lymphoblastic leukemia who undergo induction phase chemotherapy. The design of this study was descriptive analytic with repeated measurements of sleep disorders in children aged 7-18 years (n = 62). Data collection was carried out for 7 days, that is, one day before, five days during, and one day after chemotherapy. The results of data analysis found that children have > 15 minutes to fall asleep, children have less than normal amounts of sleep (the number of hours of sleep is normal, school age: 9-11 hours / day, adolescence: 8-10 hours / day) and there was a decrease in the quality of sleep scores. In conclusion, there are sleep disorders that occur in children, namely children have less time to sleep, children need a long time to be able to fall asleep, and children experience a decrease in the quality of sleep. The need for exploration of interventions to facilitate efficient sleep according to the stages of child development.